Fraudes na Previdência e Assistência Social: uma avaliação da eficácia das operações policiais no estado do Maranhão - ALMEIDA, Dhiego Melo Job de (2018)
Social security and welfare fraud carry a billion dollar losses to the public funds, with a effect on the right of a effective social security, according to the constitutional text. Like any delinquent species, social security and welfare frauds present their peculiarities, such as delinquency modalities, typologies and active criminal groups. The Federal Police acts as the judicial police body responsible for the repression of this type of crime, acting alongside the institutions of the Federal Criminal Justice System (Federal Public Ministry and Federal Justice), other partner agencies and the Social Security Task Force. In this context, the socalled Special Operations of the Judicial Police, which are nothing more than criminal investigations that comply with certain internal normative requirements of the Federal Police, acquires importance. The present dissertation evaluated twenty Special Operations set off from 2003 to 2018 by the Office of Repression of Social Security Crimes in the State of Maranhão, and concluded that if on the one hand they were effective because they resulted in indictments and denunciations, on the other they did not lead to merit decisions due to the delay in the procedural process, thus preventing a more accurate assessment of the Special Operations regarding possible convictions or acquittals.